2004
DOI: 10.1086/386372
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Induces Pneumonia, Cytokine Response, Airway Obstruction, and Chronic Inflammatory Infiltrates Associated with Long‐Term Airway Hyperresponsiveness in Mice

Abstract: This model provides a means to investigate the immunopathogenesis of RSV infection and its association with reactive airway disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
181
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(213 citation statements)
references
References 45 publications
28
181
0
4
Order By: Relevance
“…RSV infection of BALB/c mice represents a well-established experimental model, which has successfully been used to study the immunopathogenesis of RSV [23][24][25]. Lymphocytic response on day 5 post-infection and elevated levels of TNF-a, IL-6, KC and viral loads characterised RSV-infection in our study, consist with literature findings.…”
Section: Discussionsupporting
confidence: 87%
“…RSV infection of BALB/c mice represents a well-established experimental model, which has successfully been used to study the immunopathogenesis of RSV [23][24][25]. Lymphocytic response on day 5 post-infection and elevated levels of TNF-a, IL-6, KC and viral loads characterised RSV-infection in our study, consist with literature findings.…”
Section: Discussionsupporting
confidence: 87%
“…We and others have previously shown that RSV infection induces AHR in response to methacholine challenge (18,23,28). As shown in Figure 3C, we observed a significant difference between RSV-and RSV ϩ BHA-treated animals, because administration of BHA strongly attenuated RSV-induced AHR at all methacholine doses.…”
Section: Bha Attenuates Rsv-induced Clinical Illnesssupporting
confidence: 72%
“…Our results proved that mice infected with RSV before sensitization to OVA had higher AHR than non-RSV-infected mice, but other asthmatic parameters and the level of IFN-␥, IL-4, and IL-10 in BALF were not significantly different. In our previous study, we found that the concentration of IFN-␥ but not IL-4 and IL-10 increased in BALF on d 7 postinfection from mice infected with RSV as compared with noninfected controls (data not shown), which was consistent with other findings (33,35) and could be explained as acute RSV infection resulting in a Th1-type cytokine response. However, in our present experimental system, augmentation of allergeninduced AHR after RSV infection could not be explained by a Th1/Th2 mechanism.…”
Section: Discussionsupporting
confidence: 90%